2011
DOI: 10.1095/biolreprod.110.085746
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin B and Its Receptor Induce Labor Onset and Are Associated with the RELA (NFKB P65)/IL6 Pathway in Pregnant Mice1

Abstract: Although the neuromedin B receptor (NMBR), a bombesin receptor family member, has been implicated in thermoregulation and in stimulation of both urogenital and gastrointestinal smooth muscle contraction, its underlying role in labor onset and its associated molecular mechanisms remain poorly understood. We examined the relationship between temporal and spatial NMBR expression in the myometrium of pregnant mice and potential mechanistic pathways leading to labor onset. Resultant data indicate that NMBR expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…Previous studies in vivo have shown that the expression level of Nmbr reached a peak at term and decreased sharply after labor [11]. Thus, this study was conducted using primary cultures of myometrial primary cells isolated at the onset of labor immediately after parturition of the first neonate or in the interval between delivery of two pups.…”
Section: Zhang Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in vivo have shown that the expression level of Nmbr reached a peak at term and decreased sharply after labor [11]. Thus, this study was conducted using primary cultures of myometrial primary cells isolated at the onset of labor immediately after parturition of the first neonate or in the interval between delivery of two pups.…”
Section: Zhang Et Almentioning
confidence: 99%
“…It has been reported that the neuromedin B receptor (Nmbr) gene is one of the group of G protein-coupled receptors (GPCR), which are typical drug targets that are differentially expressed during parturition, while oxytocin receptor genes and other tocolytic targets do not exhibit such changes in expression [9,10]. Furthermore, the expression of Nmbr peaks at term and occurs before parturition in humans and mice, and the Nmbr agonist neuromedin B (NMB) shortens the gestational age of mice with an associated increase in DNA binding activity of Rela/p65 and Il6 mRNA expression [11]. These results suggest that the mechanism underlying the onset of labor involves changes in the expression of the Nmbr, Rela/ p65, and Il6 genes in a mouse model of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Injections were made at G13–G14, G15–G16, or G17–G18 twice a day for a total of four injections. Doses used for NmU and NmS correspond to those previously used to induce labor in mice with neuromedin B [17]. Mice were checked every 2 h for any signs of labor/delivery, such as vaginal bleeding or delivery of at least one pup.…”
Section: Methodsmentioning
confidence: 99%
“…NmU has been extensively shown to exert pleiotropic effects in the brain. Notwithstanding its known procontractile effects on rodent uterus [15], which have been suggested to be mediated by NmU-R2 [16], little is known regarding its mechanism of action in uterus and potential role in labor, but it may be relevant in the context that neuromedin B, a neuropeptide of the same family, was recently shown to induce labor in mice via its receptor NmBR [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Neuromedin B (NMB) functions through the activation of signaling pathways. For example, NMB and its receptor can induce the onset of labor via a RELA/IL6-mediated pathway (Zhang et al, 2011), and induce angiogenesis via the activation of ERK and Akt in the endothelial cells (Park et al, 2009). The NMB mRNA was detected in both the human and the rodent adipose tissue, which indicated the participation of the NMB protein in energy balance (Hoggard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%